2007
DOI: 10.1037/0022-3514.92.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and the threat of death: The cognitive dynamics of death-thought suppression and its impact on behavioral health intentions.

Abstract: Five studies examined the cognitive association between thoughts of cancer and thoughts of death and their implication for screening intentions. Study 1 found that explicit contemplation of cancer did not increase death-thought accessibility. In support of the hypothesis that this reflects suppression of death-related thoughts, Study 2 found that individuals who thought about cancer exhibited elevated death-thought accessibility under high cognitive load, and Study 3 demonstrated that subliminal primes of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 94 publications
5
96
2
2
Order By: Relevance
“…Indeed, with the addition of the research reported in this article, higher levels of DTA have now been observed following threats to people's cultural worldview, belief in a just world, romantic relationships, and self-esteem (Florian, Mikulincer, & Hirschberger, 2002;Friedman & Rholes, 2007;Hayes et al, in press;Hirschberger, 2006;Landau et al, 2004;Mikulincer et al, 2002;Schimel et al, 2007). Furthermore, exposing people to situations and events that remind them of the fragility of human existence such as cancer patients, persons with disabilities, and human creatureliness have also been shown to increase DTA (Arndt et al, 2007;Cox et al, 2007;Goldenberg et al, 1999;Hirschberger et al, 2005).…”
Section: What Types Of Threats Increase Dta?mentioning
confidence: 79%
See 1 more Smart Citation
“…Indeed, with the addition of the research reported in this article, higher levels of DTA have now been observed following threats to people's cultural worldview, belief in a just world, romantic relationships, and self-esteem (Florian, Mikulincer, & Hirschberger, 2002;Friedman & Rholes, 2007;Hayes et al, in press;Hirschberger, 2006;Landau et al, 2004;Mikulincer et al, 2002;Schimel et al, 2007). Furthermore, exposing people to situations and events that remind them of the fragility of human existence such as cancer patients, persons with disabilities, and human creatureliness have also been shown to increase DTA (Arndt et al, 2007;Cox et al, 2007;Goldenberg et al, 1999;Hirschberger et al, 2005).…”
Section: What Types Of Threats Increase Dta?mentioning
confidence: 79%
“…According to Landau et al (2004), evidence that bad things happen to good people is particularly threatening to individuals high in PNS, because it conflicts with their conception of the world as a benevolently ordered place in which people are safe and secure as long as they do what is right. Other studies consistent with the DTA hypothesis have shown that indirectly reminding people of their vulnerability to death by priming them with thoughts of cancer (Arndt, Cook, Goldenberg, & Cox, 2007), exposing them to persons with disabilities (Hirschberger, Florian, & Mikulincer, 2005), and reminding people of their animal nature (Cox, Goldenberg, Pyszczynski, & Weise, 2007;Goldenberg, Pyszczynski, McCoy, Greenberg, & Solomon, 1999), increases the accessibility of thoughts about death.…”
Section: The Death-thought Accessibility Hypothesismentioning
confidence: 87%
“…Emotion may be less important when DTA is induced through MS, subliminal death-primes or death-associated stimuli (e.g., thinking about cancer; Arndt et al 2007; terrorist attacks; Landau et al 2004; or viewing images of destruction and rubble; Vail et al 2012). Death-prime-induced DTA is believed to increase as a result of the potential anxiety invoked by death reminders (Greenberg et al 2003), whereas death-associated stimuli induce DTA via the semantic relation between the stimuli and death-related concepts.…”
Section: Implications For the Dta Hypothesismentioning
confidence: 99%
“…It has been shown that extreme primes can lead to opposite effects from more moderate primes (Herr, Sherman and Fazio 1983), that awareness of the prime can lead to contrast effects (Lombardi, Higgins, and Bargh 1987) as can priming people with exemplars instead of stereotypes or traits (Moskowitz and Skurnik 1999). Recently, the importance of taking into account motivational processes when studying priming effects has been demonstrated by the research of Arndt et al (2007) who showed that priming people with cancer can lead to suppression, instead of increased accessibility, of death-related thoughts when participants enjoy sufficient processing capacity. Our results add to this literature by showing how increased self-relevance enhances the probability of motivational, defensive mechanisms interfering with the basic priming effect.…”
Section: Implications For Priming Researchmentioning
confidence: 99%